A Novel Regulatory Circuit “C/EBPα/miR-20a-5p/TOB2” Regulates Adipogenesis and Lipogenesis - Zhou, Jie; Yang, Junying; Wang, Xiaochen; Li, Mengyue; Li, Fang; Zhu, Endong; Li, Xuemei; Li, Xiaoxia; Wang, Baoli (Frontiers in Endocrinology, 2020)
Recent studies have identified growing importance of microRNAs as key regulators of adipocyte differentiation. We have previously reported that miR-20a-5p is able to induce adipogenesis of established adipogenic cell lines and bone marrow derived mesenchymal stem cells (BMSCs). However, the molecular mechanisms by which miR-20a-5p controls adipogenesis and by which miR-20a-5p expression is regulated need to be further explored. In the current study we found that miR-20a-5p expression was induced during adipocyte differentiation from preadipocyte 3T3-L1 and was increased in epididymal white adipose tissue from either ob/ob mice or high fat diet-induced obese mice. Functional studies identified miR-20a-5p as a positive regulator of adipocyte differentiation and lipogenesis in 3T3-L1 by using either synthetic mimics to supplement miR-20a-5p, or using synthetic inhibitor or sponge lentivirus to inactivate endogenous miR-20a-5p. Luciferase activity assay revealed that TOB2 is a novel target of miR-20a-5p and functional experiment demonstrated its negative regulatory role in adipocyte differentiation. Moreover, Tob2 overexpression significantly attenuated adipocyte formation induced by miR-20a-5p supplementation. In-depth investigation of mechanisms that govern miR-20a-5p expression clarified that C/EBPα transcriptionally activated miR-20a-5p expression via binding to the promoter of miR-20a-5p. Taken together, we conclude that a novel C/EBPα/miR-20a-5p/TOB2 circuit exists and regulates adipogenesis and lipogenesis.